Chemical Pulps for Writing and Printing Papers from Eucalrptus robusta - Guha, S. R. D.; Sharma, Y. K.; Jadhav, A. G. (Indian Forester, 1965)
Laboratory expeciments on the production of chemical pulps from Ecualyptus robusta for production of writing and printing papers by sulphate process are described. The average tiher length of the pulp was 0.90 mm and the average fibre diameter was 0.010 mm. Easy bleaching pulps in good yield and satisfactory strength properties could be prepared under suitable conditions of digestion.